PENGARUH KEBIJAKAN DAN REGULASI PEMERINTAH TERHADAP PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI INKLUSI KEUANGAN - Muliana, Sitti; Anwar, Vebby; Yusti suciati ardhana akhyar (Al-Buhuts, 2023)
Women's participation in economic activities is very important. The role of women has a broad impact not only on improving the family economy and the national economy, but also in creating jobs. Indonesia, in its G20 Presidency, through its program, W20 Sispreneur, is here to create an inclusive economy to empower womenpreneurs. This program is carried out by providing easy access to capital and digital transformation. Women's empowerment in the economic sector leads to a reduction in cases of violence which have often been caused by economic problems. This research aims to examine the influence of government policies and regulations through financial inclusion on the economic empowerment of women in creative industries specifically for women in South Sulawesi. This research is a type of quantitative research. To achieve the research objectives, explanatory analysis was used using structural equation modeling (SEM-PLS) analysis tools. This research used 126 samples. The research results show that increasing government regulations regarding women's economic empowerment, policies and incentives cause women's economic empowerment to increase. The results of the structural model analysis show that financial inclusion has a positive and significant effect on women's economic empowerment.